Combined Transradial and Transfemoral Approach With Ostial Vertebral Balloon Protection for the Treatment of Patients With Subclavian Steal Syndrome - Fakih, Rami; Dandapat, Sudeepta; Mendez-Ruiz, Alan; Mendez, Aldo A.; Farooqui, Mudassir; Zevallos, Cynthia; Quispe Orozco, Darko; Hasan, David; Rossen, James; Samaniego, Edgar A.; Derdeyn, Colin; Ortega-Gutierrez, Santiago (Frontiers in Neurology, 2020)
Background: Patients with an obstructive subclavian artery (SA) may exhibit symptoms of vertebrobasilar insufficiency known as subclavian steal syndrome (SSS). Endovascular treatment with stent assisted percutaneous transluminal angioplasty (SAPTA) demonstrates significantly lower percentage of intraoperative and postoperative complications in comparison with open surgery. There is a 1-5% risk of distal intracranial embolization through the ipsilateral vertebral artery (VA) during SAPTA. Objective: To assess the safety and feasibility of a novel technique for distal embolic protection using balloon catheters during SA revascularization with a dual transfemoral and transradial access. Methods: We describe a case series of patients with SSS who underwent SAPTA due to severe stenosis or occlusion of the SA using a combined anterograde/retrograde approach. Transfemoral access to SA was obtained using large bore guide sheaths. Ipsilateral transradial access was obtained using intermediate bore catheters. A Scepter XC balloon catheter was introduced through the transradial intermediate catheter into the ipsilateral VA at the ostium during SAPTA for distal embolic protection. Results: A total of eight patients with SSS underwent subclavian SAPTA. Four patients had the combined anterograde/retrograde approach. Successful revascularization was achieved in three of them. It was difficult to create a channel in the fourth unsuccessful case due to heavily calcified plaque burden. No peri-operative ischemic events were identified. On follow-up, we demonstrated patency of the stents with resolution of symptoms and without any adverse events. Conclusion: Subclavian stenting using a combined transradial and transfemoral access with compliant balloon catheters at the vertebral ostium for prevention of distal emboli may represent an alternative therapeutic approach for the treatment of SA stenosis and occlusions.